O conceito de matéria na Filosofia da natureza de Immanuel Kant - Brito, Gilberto do Nascimento Lima (2021)
This dissertation aims to demonstrate the importance of the concept of matter to a proper understanding of a physical-mechanical nature which has its principles in the Critique of Pure Reason and his development exposed in the work Metaphysical Principles of the Science of Nature, work is dedicated exclusively to the study of this concept. In other words, the analysis of the concept of nature in which the concept of matter is inserted to require the study of the two works; soon, so our project is done, makes it also necessary to treat the concepts that precede and provide the assumptions for the concept of matter can be treated in the Metaphysical Principles of the Science of Nature. Therefore, before we properly treat the concept of matter, we reveal the relation that such a concept has with some of the founding principles of a general theory of knowledge established in the Critique of Pure Reason. It is in this context that we address concepts such as time, space, imagination, categories and understanding. Elements seemingly distant from the concept of matter, but that are essential so that it can be properly understood.